Penyembuhan Luka Grade 2 pada Pasien Diabetes Mellitus dengan Modern Dressing Wound Care - I Dewa Ayu Rismayanti; I Made Sundayana; Putu Eka Pratama (Jurnal Keperawatan Silampari, 2020)
This study aims to determine the effect of modern dressings on wound healing of grade 2 diabetes mellitus at Griya Utami Care Bali. The design used in the study was a real experiment with a one-group pre-post test approach. The results showed that the experimental group's average post value was 8.67, with a standard deviation of 2.024. In the control group, the average post value was 10.60, with a standard deviation of 2.874. Based on the results of statistical tests, it was found that the p-value was 0.042, meaning that there was a significant difference in the average post value between the experimental group and the control group. In conclusion, there is an effect of modern dressings on wound healing for grade 2 diabetes mellitus at Griya Utami care Bali. Keywords: Diabetes Mellitus, Grade 2 Diabetes Wounds, Modern Dressing